Etika in svoboda v politični misli Franceta Vebra - Jeršič, Alja (Analiza (Ljubljana), 2025)
This paper focuses on the moral philosophy of France Veber, addressing his understanding of freedom and ethics, as well as related concepts such as conscience, duty, value-based emotion, and aspiration, along with the questions that he examined in the ethical-moral context. Veber rejected both the eudaimonistic and the utilitarian conceptions of ethics, as he did not regard happiness as the ultimate goal of moral action – in his view, the ethical value of an act lies in its motive rather than its consequences. His ethical stance is also reflected in his political thought, as he criticized the idea that a nation, state, or humanity as a whole could strive for happiness. In doing so, he rejected collectivist political concepts that subordinate the individual to higher entities. Marxist circles dismissed his philosophy as reactionary even before the war. Veber was irritated by party conflicts and did not identify with any political party. He blamed materialism for war and social misery, which, in his opinion, resulted from a one-sided pursuit of material gain and the neglect of spiritual values – the very values he emphasized in his reflections on freedom and ethics.
Keywords: conscience; Dolžnost; Etika; moral philosophy; moralna filozofija; Svoboda; Veber, France; vest